Clomiphene citrate and neural tube defects: a meta‐analysis of controlled observational studies. (23rd May 2019) - Auffret, M; Cottin, J; Vial, T; Cucherat, M
Abstract : Background: At the end of the 1980s, several studies suggested a potential increased risk of neural tube defects (NTDs) with ovulation induction/fertility drugs, especially with clomiphene citrate (CC). A previous meta‐analysis of observational studies evaluating the risk of NTDs associated with the use of CC performed in 1995 found a risk ratio of 1.08 (95% CI 0.76–1.51). Since then, additional studies have been published and the risk of NTDs associated with periconceptional CC exposure may have changed. Objective: To perform an updated quantitative meta‐analysis of the risk of NTDs associated with periconceptional CC exposure. Search strategy: MEDLINE, Web of Science, and Scopus were searched (October 2018). Selection criteria: Comparative cohort and case–control studies investigating the risk of NTDs after periconceptional CC exposure. Data collection and analysis: Pooled effect sizes with corresponding 95% CIs were calculated using random effects models, comparing the risk of NTDs between pregnancies exposed and not exposed to CC. Main results: Thirteen studies met the inclusion criteria, totalling 218 819 pregnancies. Periconceptional exposure to CC was not significantly associated with an increased risk of NTDs (pooled odds ratio 1.21, 95% CI 0.88–1.66). No heterogeneity between studies was observed ( I 2  = 26%). A funnel plot and asymmetry test were not suggestive of publication bias. Conclusion: Our meta‐analysis confirms that exposure to CC before or in early pregnancy was associated with a 21% increased risk of NTD in relation to CC exposure; however, this increased risk is not statistically significant. Tweetable abstract: A new meta‐analysis finds that clomiphene citrate exposure before or in early pregnancy is not associated with an increased risk of NTDs. Tweetable abstract: A new meta‐analysis finds that clomiphene citrate exposure before or in early pregnancy is not associated with an increased risk of NTDs.